Trajectories of cognitive performance over five years in a prospective cohort of patients with breast cancer (NEON-BC). (August 2021) - Araújo, Natália; Severo, Milton; Lopes-Conceição, Luisa; Fontes, Filipa; Dias, Teresa; Branco, Mariana; Morais, Samantha; Cruz, Vítor Tedim; Ruano, Luis; Pereira, Susana; Lunet, Nuno
Abstract: Purpose: To identify trajectories of cognitive performance up to five years since diagnosis and their predictors, in a cohort of patients with breast cancer (BCa). Methods: A total of 464 women with BCa admitted to the Portuguese Institute of Oncology, Porto, during 2012, were evaluated with the Montreal Cognitive Assessment (MoCA) before any treatment, and after one, three and five years. Probable cognitive impairment (PCI) at baseline was defined based on normative age- and education-specific reference values. Mclust was used to define MoCA trajectories. Receiver Operating Characteristic curves were used to assess the predictive accuracy for cognitive trajectories. Results: Two trajectories were identified, one with higher scores and increasing overtime, and the other, including 25.9% of the participants, showing a continuous decline. To further characterize each trajectory, participants were also classified as scoring above or below the median baseline MoCA scores. This resulted in four groups: 1) highest baseline scores, stable overtime (0.0% with PCI); 2) lowest baseline scores (29.5% with PCI); 3) mid-range scores at baseline, increasing overtime (10.5% with PCI); 4) mid-range scores at baseline, decreasing overtime (0.0% with PCI). Adding the change in MoCA during the first year to baseline variables significantly increased the accuracy to predict the downward trajectory (area under the curve [AUC] = 0.732 vs. AUC = 0.841, P < 0.001). Conclusion: Four groups of patients with BCa with different cognitive performance trends were identified. The assessment of cognitive performance before treatments and after one year allows for the identification of patients more likely to have cognitive decline in the long term. Highlights: 5-year cognitive trajectories since diagnosis of breast cancer were identified. 25.9% of breast cancer survivors had a declining cognitive trajectory. Cognitive performance during the 1st year predicted the 5-year trajectory.